Mapping the Extent of Land Degradation in East Baton Rouge Parish - E. Dadzie; Y. A. Twumasi; Z. H. Ning; J. D. Osei; D. T. Gyan; D. Aniewu; P. M. Loh (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Land degradation poses a significant threat to the sustainability of ecosystems and agricultural productivity, particularly in regions undergoing rapid urbanization. In East Baton Rouge Parish, the pressures of urban expansion and shifting land use patterns have intensified the degradation of natural landscapes. This study examines land degradation in East Baton Rouge Parish, Louisiana, over a 30-year period, with a specific focus on the impact of urban expansion on vegetation health. Using remote sensing techniques, including the Normalized Difference Vegetation Index (NDVI) and the Soil-Adjusted Vegetation Index (SAVI), this research quantifies the extent and spatial distribution of land degradation, highlighting shifts in land use and land cover. Results show a −13.62% decrease inclosed forest areas, primarily attributed to urban expansion, alongside a 3.47% increase in built-up areas. This transition has led to increased impervious surfaces, which exacerbate soil erosion, reduce biodiversity, and raise flood risks due to altered hydrological patterns. The 9.88% increase in open forest suggests partial vegetation regrowth or thinning of dense forest, though it does not fully counterbalance the ecological losses from closed forest reduction. These findings emphasize the need for targeted restoration efforts,such as reforestation and green infrastructure, to mitigate further degradation. This study offers critical insights for policymakers and environmental planners aiming to mitigate land degradation and promote the long-term sustainability of East Baton Rouge Parish’s ecosystems.